PEMANFAATAN ALGINAT DARI ALGA COKLAT(SARGASSUM SP) UNTUK PRODUKSI PLASTIK YANG BIODEGRADABLE - Essye Dwiwahyu R, Mita Suryani, Ratna Dwi W, Eli Rohaeti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
The developing of biodegradable plastic is an alternative to overcome the problemon the abundance of plastic in environment. This research aims to 1) learn the productionprocess of biodegradable plastic from alginat, 2) learn the easy of biodegradation processfrom plastic material, 3) learn the influence of the length of biodegradation toward theweight loss of plastic from alginat, and 4) compare the degradability between LLDPE((Low Liniear Density Polyethylene) plastic and HDPE (High Density Polyethylene).Alginat was from the extraction of brown algae and Na2CO3 12% , then it was madeas gel by adding HCL 10%. The production process of biodegradable plastic was done byblending-tecnique (LLDPE dan HDPE) with alginat. The test of biodegradable plasticwas done by piling soil up for six days. The speed of weight loss of plastic was shown bythe percent of plastic weight loss.The quatitative analysis of alginat isolated from brown algae with concentration1;, 0.75; 0.5; 0.25 and 0.125% produces the viscosity 2.48; 2.05; 1.89; 1.71; dan 1.62poise, and also specific gravity of alginat 1.085; 1.081; 1.078; 1.083; and 1.078 g/ml. Thebiodegradation result of LLDPE, HDPE, LLDPE plus Alginat and HDPE plus Alginatfind the average of weight loss for three days are 9.03; 4.76; 0; and 16.86%, and for sixdays 0; 0.75; 9.45; and 6.08%. The biodegradable plastic with HDPE plus alginat isbiodegraded faster because of having short chain of ramification.Key words: brown algae, alginat, biodegradable